Amantadine ER (Gocovri®) Significantly Increases ON Time Without Any Dyskinesia: Pooled Analyses From Pivotal Trials in Parkinson's Disease - Hauser, Robert A.; Walsh, Ryan R.; Pahwa, Rajesh; Chernick, Dustin; Formella, Andrea E. (Frontiers in Neurology, 2021)
Background Clinical trials for antiparkinsonian drugs aimed at managing motor complications typically use patient diaries to divide levodopa-induced dyskinesias (LID) into ‘troublesome’ and ‘non-troublesome’ categories. Yet, given the choice, most patients would prefer to live without experiencing any dyskinesia. However, the concept of evaluating time spent ON without any dyskinesia as an outcome has never been tested. We conducted analyses of pooled ADS-5102 trial data in order to evaluate the extent to which ADS-5102 increased the time PD patients spent ON without dyskinesia (troublesome or non-troublesome), beyond its already identified improvement in reducing troublesome dyskinesia. Methods Patients enrolled in phase 3 trials (EASE-LID [NCT02136914] or EASE-LID 3 [NCT02274766]) recorded time spent in the following PD diary states at baseline and Week 12 (endpoint): asleep, OFF, ON with troublesome dyskinesia, ON with non-troublesome dyskinesia, and ON without dyskinesia. Mixed model repeated measures analyses with estimated Cohen D effect sizes were performed on the modified intent to treat population to evaluate changes in time spent in these states. Results Patients randomized to receive ADS-5102 showed an increase in ON time without dyskinesia and corresponding decreases in ON time with dyskinesia and OFF time versus placebo. Treatment effects were statistically significant for ADS-5102 versus placebo starting at Week-2 and were sustained until Week-12. On MMRM analysis at Week-12, patients in the ADS-5102 group showed an adjusted mean ± SE increase over placebo of 2.9 ±0.6 hours in ON time without dyskinesia (Cohen D effect size 0.89) and an adjusted mean ±SE decrease of -1.9 ±0.6 hours in ON time with dyskinesia (troublesome + non-troublesome) (Cohen D effect size 0.49), that included a -1.5 ±0.4 hour placebo-adjusted reduction in ON time with troublesome dyskinesia and a -0.6 ±0.4 hour reduction in ON time with non-troublesome dyskinesia. OFF time was reduced by -1.0 ±0.3 hours compared to placebo. Conclusions ADS-5102 treatment more than doubled the daily time patients spent ON without dyskinesia. These results suggest that the ADS-5102 treatment effect was driven by a reduction in overall motor complications including ON time with both troublesome and non-troublesome dyskinesia as well as time spent OFF.